Singing Methods in Improving Personal Hygiene Independence in School-Age Children - Hera Hijriani; Aat Agustini; Idris Handriana; Wawan Kurniawan; Je'an Zeina Fahira (Jurnal Keperawatan Silampari, 2023)
This study aims to understand the effect of the singing method on independence in the personal hygiene of school-age children in Leuwikidang Village, Majalengka Regency, in 2022. The technique used is a quantitative and cross-sectional approach using a purposive sampling technique. The results showed that the percentage of independence in personal hygiene for children was carried out before carrying out health education using the singing method (53.3%) and after carrying out health education using the singing method (60.0%). In conclusion, there is a significant influence on the personal hygiene independence of school-age children in Leuwikidang Village with health education and the singing method. Keywords: School Age Children, Personal Hygiene Independence, Singing Method